Combined hyperpolarized 13C-pyruvate MRS and 18F-FDG PET (hyperPET) estimates of glycolysis in canine cancer patients. Issue 103 (June 2018) - Hansen, Adam E.; Gutte, Henrik; Holst, Pernille; Johannesen, Helle H.; Rahbek, Sofie; Clemmensen, Andreas E.; Larsen, Majbritt M.E.; Schøier, Christina; Ardenkjaer-Larsen, Jan; Klausen, Thomas L.; Kristensen, Annemarie T.; Kjaer, Andreas
Graphical abstract: Highlights: Hyperpolarized 13 C-pyruvate MRS and FDG-PET was compared in canine cancer patients. Lactate generation and FDG uptake correlated for a certain cancer type only. The relation between lactate generation and FDG uptake depended on cancer type. HyperPET estimates of glycolysis may allow for improved metabolic phenotyping. Abstract: 13 C Magnetic Resonance Spectroscopy (MRS) using hyperpolarized 13 C-labeled pyruvate as a substrate offers a measure of pyruvate-lactate interconversion and is thereby a marker of the elevated aerobic glycolysis (Warburg effect) generally exhibited by cancer cells. Here, we aim to compare hyperpolarized [1- 13 C]pyruvate MRS with simultaneous 18 F-2-fluoro-2-deoxy-d -glucose (FDG) PET in a cross-sectional study of canine cancer patients. Methods: Canine cancer patients underwent integrated PET/MRI using a clinical whole-body system. Hyperpolarized [1- 13 C]pyruvate was obtained using dissolution-DNP. 18 F-FDG PET, dynamic 13 C MRS, 13 C MRS Imaging (MRSI) and anatomical 1 H MRI was acquired from 17 patients. Apparent pyruvate-to-lactate rate constants were estimated from dynamic 13 C MRS. 18 F-FDG Standard Uptake Values and maximum [1- 13 C]lactate-to-total- 13 C ratios were obtained from tumor regions of interest. Following inspection of data, patients were grouped according to main cancer type and linear regression between measures of lactate generation and 18 F-FDG uptake were tested within groups. Between groups, the same measures were tested for group differences. Results: The main cancer types of the 17 patients were sarcoma (n = 11), carcinoma (n = 5) and mastocytoma (n = 1). Significant correlations between pyruvate-to-lactate rate constants and 18 F-FDG uptake were found for sarcoma patients, whereas no significant correlations appeared for carcinoma patients. The sarcoma patients showed a non-significant trend towards lower 18 F-FDG uptake and higher lactate generation than carcinoma patients. However, the ratio of lactate generation to 18 F-FDG uptake was found to be significantly higher in sarcoma as compared to carcinoma. The results were found both when lactate generation was estimated as an apparent pyruvate-to-lactate rate constant from dynamic 13 C MRS and as an [1- 13 C]lactate to total 13 C ratio from 13 C MRSI. Conclusions: A comparison of hyperpolarized [1- 13 C]pyruvate MRS with simultaneous 18 F-FDG PET indicate that lactate generation and 18 F-FDG uptake in cancers can be related and that their relation depend on cancer type. This finding could be important for the interpretation and eventual clinical implementation of hyperpolarized 13 C. In addition, the differences between the two modalities may allow for better metabolic phenotyping performing hybrid imaging in the form of hyperPET.